Assessing the impact of resistance training on renal function of female wistar rats under cross-sex hormone therapy - Almeida, Isadora Gonçalves; Silveira, Isabela Borges M.; Cordeiro, Emily Rocha; Monteiro, Letícia Maria; da Silva, Nathalia Beserra; Argeri, Rogerio; Lichtenecker, Debora C. K.; Dias da Silva, Magnus R.; Gomes, Guiomar Nascimento (Frontiers in Physiology, 2025)
IntroductionCross-hormone therapy (CHT) is commonly used in the gender-affirming process, with testosterone being administered to trans men to develop secondary masculine characteristics. In experimental models replicating this condition, CHT has been associated with increased plasma creatinine levels and renal morphological changes. Given benefits of physical exercise, this study aimed to evaluate whether resistance training could mitigate CHT-induced renal alterations.ObjectivesTo investigate the impact of resistance training combined with CHT on blood pressure and renal morphology and function.MethodsTwo-month-old female Wistar rats were divided into four groups: FSV–sedentary rats treated with vehicle (vegetable oil); FSH–sedentary rats treated with CHT; FEV–exercised rats treated with vehicle; and FEH–exercised rats treated with CHT. CHT was administered via testosterone cypionate (3.0 mg/kg, intramuscularly) every 10 days for 8 weeks. Exercise groups underwent progressive resistance training using a vertical climbing ladder five times per week for 6 weeks. At the end of the protocol, the animals were placed in metabolic cages for urine collection, followed by blood sampling for biochemical analysis.ResultsTestosterone-treated groups showed increased plasma creatinine levels, though urea concentrations were unchanged. Plasma sodium concentration was elevated, and sodium excretion was reduced in the sedentary testosterone-treated group. Morphological analysis revealed that resistance exercise reduced macrophage infiltration, lowered the number of PCNA-positive cells in kidney tissue, and decreased glomerular tubularization in the kidney.ConclusionTestosterone-based CHT in female rats induces renal functional alterations, but resistance exercise effectively attenuates these effects by reducing macrophage infiltration, cell proliferation, and glomerular changes.